Studying Mothers' Knowledge and Perceptions of Adolescent Reproductive Health - Hartaty, Diana; Martha, Evi (Asosiasi Pendidikan Kebidanan Indonesia (AIPKIND), 2024)
Correction of: https://wmmjournal.org/index.php/wmm/article/view/142 DOI: https://doi.org/10.36749/wmm.4.1.8-16.2024 Background: Reproductive health education is obtaining information and forming attitudes and beliefs about sex, sexual identity, relationships, and intimacy. Mothers are the primary caregivers and have an essential role in providing reproductive health and sexual education to adolescents. Parents' lack of reproductive health education triggers deviation; therefore, parents, especially mothers, can provide comprehensive reproductive health education to prevent free sexual behaviour and sexual crimes in adolescents. Purpose: To measure the knowledge and perception of mothers about adolescent reproductive health Methods: This is a cross-sectional study with a descriptive design. The study involved 135 respondents who were selected using a purposive sampling technique. Analysis using descriptive, T-test and Pearson correlation. Results: More than 50% of respondents answered that adolescents' reproductive health education should be parents' responsibility and education should begin during elementary school. There was a correlation between mothers' knowledge and perception of adolescent reproductive health (r=0.44, p<0.001). Most mothers were afraid of providing sex education due to their ignorance of teaching methods and their lack of knowledge, and mothers wanted to learn about adolescent reproductive health from experts. Conclusion: Mothers want to learn more about sex education from experts or health workers. They were interested in male/female sexual structure and sexual physiology. Open communication between mother and child on sex-related issues is essential. Providing accurate and up-to-date sex education information to parents is vital to effectively educating their children at home.